Lessons from Nature: Advances and Perspectives in Bionic Microwave Absorption Materials - Dashuang Wang; Tuo Ping; Zhilan Du; Xiaoying Liu; Yuxin Zhang (Nano-Micro Letters)
Highlights This review describes the classification of bionic objects of bionic wave-absorbing materials in detail. From marine organisms, insects, plants to animals, different bionic objects will bring diversified influences and applications. The multifunctional applications of bionic microwave absorption materials are systematically introduced in this paper, from microwave absorption to anti-corrosion, to mechanics, electronics, wearable devices, etc. The theoretical basis and simulation calculation of bionic microwave absorption materials are also discussed.